Evaporation of nanofluids - Choong, Clarrisa Yu Ying. (2013)
Nanofluids are suspensions of nanoparticles in fluids that exhibit significant enhancement of their properties at modest nanoparticle concentrations. They are utilized in electronic applications as cooling devices in combination with thin film evaporation and in industrial applications where overheated surfaces in power plants are cooled down more quickly. In an effort to elucidate nanofluid droplet evaporation characteristics, this study presents experimentation on the evaporation of nanofluids. The main objective is to examine how varying parameters affect the evaporation of nanofluids in terms of contact angle, base diameter and volume.